Understanding English grammar : a linguistic approach - Wardhaugh, Ronald. (Blackwell, 1995)
Preliminaries. Word classes. Constituents and phrases. Basic clauses. Coordination and embedding. Clausal variation. Underlying relationships. Rules and principles. Sounds and systems. Phonetic realization. Word formation. Words and sounds. Sounds in context.